Sistem Pencegahan Kecelakaan Pada Remaja Dengan Pemantauan Kecepatan Kendaraan Berbasis GPS dengan Pesan Sebagai Media Pengiriman Data (Studi Kasus : Sekolah SMK Tritech Informatika Medan) - Dedi Leman; Labuan Nababan (RJOCS (Riau Journal of Computer Science), 2019)
In adolescence humans cannot be called adults but also cannot be called children. Adolescence is a human transition from children to adults. Nowadays someone is looking for identity, many teenagers are wrong in getting along, including racers, because teens that use transportation are one of the choices of the community to support their daily activities. The number of transportation accidents on the highway Indonesia can answer high. Repair motorbikes and increase speed on city roads so that it is directly proportional to avoiding accidents. To reduce the number of accidents because the driver is increasing, it is necessary to improve the driver Follow the Attendance System, the parties involved can find out about the driver and often provide proven facts about the specified speed limit. The Global Positioning System (GPS) application in the transportation sector, especially in the speed system for motorbike riders, is an integration of three technologies, namely GPS positioning technology